A Moderate Defence of the Use of Thought Experiments in Applied Ethics - Walsh, Adrian (Ethical theory and moral practice, 2011)
Thought experiments have played a pivotal role in many debates within ethics—and in particular within applied ethics—over the past 30 years. Nonetheless, despite their having become a commonly used philosophical tool, there is something odd about the extensive reliance upon thought experiments in areas of philosophy, such as applied ethics, that are so obviously oriented towards practical life. Herein I provide a moderate defence of their use in applied philosophy against those three objections. I do not defend all possible uses of thought experiments but suggest that we should distinguish between legitimate and illegitimate uses. Their legitimate uses are determined not so much by the modal content of any actual thought experiment itself, but by the extent to which the argument in which it is nested follows basic tenets of informal logic and respects the fundamental contingency of applied ethical problems. In pursuing these ideas, I do not so much provide a set of criteria for their legitimate use, but more modestly present two significant ways in which their use can go awry.